Mechanical characterization and fatigue assessment of wire and arc additive manufactured HSLA steel parts - Rodideal, Nicolae (2020)
Additive manufacturing is one of the main foundations of Industry 4.0. It aims, particularly, to increase productivity, reducing material waste due to machining and bring many advantages that overcome the conventional manufacturing processes. Wire and Arc Additive Manufacturing (WAAM) is an additive manufacturing process that employs an electric arc as heat source in order to melt and add material. It shows great versatility and freedom to fabricate parts using a layer-by-layer method of deposition. Despite the clear advantages presented, there still needs more progress in order to make it industrially feasible. One of the main challenges it faces is studying the mechanical properties bet on the desired geometry, type of material and the adopted parameters before employing these components in critical operational loading conditions. This dissertation aimed to assess the mechanical properties and fatigue resistance of HSLA parts manufactured by this technology. In this way, two type of samples were produced – one of low heat-input and another of high heat-input, in which the changing variable was the travel speed. For each type, three thin walled parts were obtained, measuring 180 x 100 mm each. After manufacturing all the required samples, three different regions were analysed – bottom, middle and top. Next, all parts were assiduously prepared in order to proceed with material characterization as well as testing, specifically, waviness, microstructure, electrical conductivity, microhardness, uniaxial tensile tests and lastly fatigue tests, with subsequent fracture surface observation through Scanning Electron Microscope (SEM). Fatigue tests were performed at room temperature on low heat-input samples with constant stress amplitude, stress ratio R=0.1 and frequencies between 12 Hz and 15 Hz. The S-N curve of the experimental results is presented along with an explanation within the context of the other characterization techniques results.